Development of a novel scoring system to determine the optimal timing of esophagogastroduodenoscopy following portosystemic shunt occlusion - Tatsuro Nishimura; Aika Kirihara; Maho Egusa; Natsuko Nishiyama; Tsuyoshi Fujioka; Daiki Kawamoto; Ryo Sasaki; Norikazu Tanabe; Issei Saeki; Toshihiko Matsumoto; Tsuyoshi Ishikawa; Taro Takami (PLoS ONE, 2026)
Balloon-occluded retrograde transvenous obliteration (BRTO) is a safe and effective treatment for gastric varices (GV) and refractory hepatic encephalopathy (HE) associated with portosystemic shunt (PSS). However, esophageal varices (EV) worsening after BRTO is a major, postoperative complication. This study aimed to develop a novel scoring system for predicting EV deterioration following PSS occlusion and to determine the optimal timing for esophagogastroduodenoscopy (EGD) after the operation for patients with portal hypertension. We retrospectively analyzed data from 76 patients with PSS who underwent BRTO for GV or refractory HE [male/female = 39/37; Child-Pugh class A/B/C = 37/32/7; mean Hepatic venous pressure gradient = 10.8 mmHg] at our institution between April 2008 and March 2021. Factors associated with EV deterioration after BRTO were identified statistically. Cumulative rates of EV deterioration were determined using the Kaplan-Meier method. During a median follow-up period of 18.0 months, 50 patients experienced EV deterioration. The median time to EV deterioration was 23.4 months. Cumulative rates of EV deterioration at 12, 24, and 36 months were 35.5%, 51.5%, and 58.1%, respectively. Multivariate analysis using a Cox proportional hazards model identified male sex ( p = 0.013), a preoperative platelet count ≤ 8.3x10⁴/μL ( p = 0.032), and presence of EV before BRTO ( p = 0.029) as significant independent risk factors for postoperative EV deterioration. Based on these three factors, we developed a novel scoring system ranging from 0–3 points. Median time to EV deterioration for scores 0, 1, 2, and 3 was unreached, 19.2, 10.2, and 6.5 months, respectively. Post-BRTO EV deterioration can be predicted using three factors: male sex, a preoperative platelet count ≤ 8.3x10⁴/μL, and the presence of EV before BRTO. This novel scoring system provides a structured approach for determining the optimal timing of EGD after BRTO, allowing risk stratification, improved postoperative patient management, early detection of EV deterioration, and timely endoscopic intervention for high-risk varices.